The Role of Athletic Knowledge Management in Obtaining a Competitive Advantage in the Sports Work Environment - Hamza Akram; Ahmed Usman Khan; Fatima Naveed; Arsalan Khalid (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2022)
The capacity of successful sports companies to maintain their competitive advantage over time and achieve their goals is directly correlated to the level of knowledge management such organizations use. This study's purpose is to investigate the management of athletic knowledge and the necessity of doing so in Pakistan in order to gain a competitive advantage in the sports business. Specifically, the research will focus on the following: The study sample is comprised of sixty male and female students who are currently enrolled inside the Sports Organization and Management Course at a several of higher education institutions in Lahore, Pakistan. These students are from different universities which are studied in HEIs (Higher Education Institutions) of Lahore Pakistan. The research was carried out using a quantitative approach because of the kind of the data that was gathered. To better understand how athletic knowledge management may be used to gain an edge in the sports industry, and how it can be used to improve the sports industry as a whole, a survey was sent to respondents that split its focus between these two areas. The overwhelming majority of respondents, 98%, are in agreement that effective knowledge management is necessary for achieving a competitive advantage in the sports work environment and for making improvements to the sports work environment. In addition, the data imply that knowledge management adds greatly to both the operations of knowledge management and the growth of the sports workplace. According to the findings, there are no distinguishing characteristics between males and females that can be supported by statistical analysis. There have been a number of key proposals made, one of the most important of which is the provision of safe, stable, methodical, and planned conditions for all courses in order to enhance and improve the athletic performance of employees. In order to materialize this concept, the upper management of the organization must place the provision of both physical and moral structure at the very top of their list of responsibilities